A new species of Bomarea (Alstroemeriaceae) from an historically documented location in Ecuador - Fierro-Minda, Alisson; Tribble, Carrie M.; Guerrero-Molina, Tomás; Tobar, Francisco; Pérez, Álvaro J. (Phytotaxa, 2025)
N/A